2003
DOI: 10.1897/00-361
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of model performance for six quantitative structure‐activity relationship packages that predict acute toxicity to fish

Abstract: Abstract-Some regulatory programs rely on quantitative structure-activity relationship (QSAR) models to predict toxic effects to biota. Many currently existing QSAR models can predict the effects of a wide range of substances to biota, particularly aquatic biota. The difficulty for regulatory programs is in choosing the appropriate QSAR model or models for application in their new and existing substances programs. We evaluated model performance of six QSAR modeling packages: Ecological Structure Activity Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 41 publications
(69 reference statements)
0
57
0
1
Order By: Relevance
“…Papers that use expert systems for estimation of aquatic toxicity are reviewed below. Moore et al [95] published a comparative analysis on model performance of six software packages that predict acute toxicity to fish [ECOlogical Structure -Activity Relationships (ECOSAR), TOPKAT, two neural networks, ASsessment Tools for the Evaluation of Risk (ASTER) and OASIS]. A probabilistic neural network was found to be the best predictor for external chemicals.…”
Section: Examples Of Expert Systemsmentioning
confidence: 99%
“…Papers that use expert systems for estimation of aquatic toxicity are reviewed below. Moore et al [95] published a comparative analysis on model performance of six software packages that predict acute toxicity to fish [ECOlogical Structure -Activity Relationships (ECOSAR), TOPKAT, two neural networks, ASsessment Tools for the Evaluation of Risk (ASTER) and OASIS]. A probabilistic neural network was found to be the best predictor for external chemicals.…”
Section: Examples Of Expert Systemsmentioning
confidence: 99%
“…Prediction of toxicity as a result of the bio-activation of chemicals that occurs during metabolism is relatively straightforward, and can be achieved to a good degree of accuracy using in silico programs such as DERECK, TOPCAT or HazardExpert [5][6][7]. However and area of increasing concern are toxic reactions caused due to interactions between coadministered chemicals.…”
Section: General Introductionmentioning
confidence: 99%
“…These models were sufficiently successful to be used for the quantitative estimation of FHM values for a large number of DSL substances. Furthermore, a very detailed study employing a variety of statistical measures by Moore et al [9], and using an external test set of 130 substances derived from other sources, showed that the PNN results were superior in almost all aspects when compared to the other models predictions, including those of ECOSAR [3], ASTER [10], and TOPKAT [11]. These results clearly demonstrate both the general ability of neural network methods to be capable of modeling such diverse data sets and the specific ability of the PNN in doing so.…”
Section: A Qsars Of Fathead Minnow Lc50 Datamentioning
confidence: 99%
“…It has not yet been part of any comparative study, such as the one by Moore et al [9], however a graph showing the estimated and measured values for the training data set is provided in the manual of that program and indicates a high degree of correlation.…”
Section: A Qsars Of Fathead Minnow Lc50 Datamentioning
confidence: 99%